H Pengaruh Profitabilitas, Pembayaran Dividen, Arus Kas Bebas, dan Leverage terhadap Manajemen Laba dengan Komisaris Independen sebagai Variabel Moderasi: Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Hartawan Ansar; Nurleni Nurleni; Haerial Haerial (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2023)
This research aimed to examine and analyze the effect profitability, dividend payments, free cash flow and leverage on the profit management with independent commissioner as the moderating variable. The sample collection method used purposive sampling used a purposive sampling method it obtained 136 companies sample as the research object. On the other hand, the analysis technique of this research used multiple linear regressions analysis and Moderated Regression Analyze (MRA). The result of multiple linear regressions this research found that profitability partially had significant effect on profit management. free cash flow partially had significant effect on profit management. dividend payments and leverage no significant effects on ptofit management. Furthermore, the result of MRA ( Moderated Regression Analyze) test concluded that independent commissioner was incapable to moderate the correlation between profitability and leverage on profit management. Keywords: profitability, dividend payment, free cash flow, and leverage, independent commissioner